The integrated National NeuroAIDS Tissue Consortium database: a rich platform for neuroHIV research. (8th January 2019) - Heithoff, Abigail J; Totusek, Steven A; Le, Duc; Barwick, Lucas; Gensler, Gary; Franklin, Donald R; Dye, Allison C; Pandey, Sanjit; Sherman, Seth; Guda, Chittibabu; Fox, Howard S
Abstract: Herein we present major updates to the National NeuroAIDS Tissue Consortium (NNTC) database. The NNTC's ongoing multisite clinical research study was established to facilitate access to ante-mortem and post-mortem data, tissues and biofluids for the neurohuman immunodeficiency virus (HIV) research community. Recently, the NNTC has expanded to include data from the central nervous system HIV Antiretroviral Therapy Effects Research (CHARTER) study. The data and biospecimens from CHARTER and NNTC cohorts are available to qualified researchers upon request. Data generated by requestors using NNTC biospecimens and tissues are returned to the NNTC upon the conclusion of requestors' work, and this external, experimental data are annotated and curated in the publically accessible NNTC database, thereby extending the utility of each case. A flexible and extensible database ontology allows the integration of disparate data sets, including external experimental data, clinical neuropsychological and neuromedical testing data, tissue pathology and neuroimaging data.